Identifying the attributes of success of Saudi female entrepreneurs in garment production: an exploratory study conducted in Saudi Arabia - Alzahrani, Sarah G. (Kansas State University, 2012)
This study documents Saudi women who have succeeded in operating their own small businesses, namely in the production of apparel goods. The study notes the reasons that motivate women to establish this kind of work and the factors that help women to be successful in apparel production in Saudi Arabia. Additionally, the study explores the challenges that women encounter in the apparel production field, as well as the commitment women have to offering employment to Saudi girls and young women. This study is important given a lack of appropriate employment opportunities for women in Saudi Arabia and the weak rate of women’s participation in the workforce in Saudi Arabia. Qualitative data was collected to gain in-depth information about the characteristics of successful female entrepreneurs in Saudi Arabia. The current study also adds new insight related to entrepreneurial success and failures, stemming from factors identified by participants. As part of the study, it was discovered that Saudi female entrepreneurs were motivated by financial and non-financial factors, pull and push, and internal and external motives. Personal characteristics of the business owner, the quality of the product produced within the firm, advertising and promotion strategies, family support, previous education, availability of resources, and years of experience were all elements identified by participants as contributing to their success. Obstacles suffered by participants included competition, filing government paperwork, conflict between roles at work and home, marketplace changes, and lack of management skills. Finally, when asking the participants about their ability or willingness to extend their work to accommodate larger numbers of Saudi women, it was found that the business owners had several reasons for not planning to do this, including the lack of the skills needed for this industry upon Saudi women and the preference of Saudi women to work in the service sector.
Keywords: Saudi , Women, Apparel production, Entrepreneur; Textile Research (0994)